Optimizing the quality of inclusive education services in Kendari City through the SERVQUAL approach - Agussalim, Anggit Aulia; Hasniati, Hasniati (Journal of Law Science, 2024)
Inclusive education is part of a global movement to ensure equal access for all children, including those with special needs. This study aims to explore and analyze the quality of inclusive education services in Kendari City using the SERVQUAL approach and to provide strategic recommendations for improving services for students with special needs. The SERVQUAL approach assesses five dimensions of service: reliability, responsiveness, assurance, empathy, and tangibles. Despite strong government commitment, challenges remain, such as a lack of Special Education Teachers (GPK) and inadequate facilities. By evaluating existing services through SERVQUAL, this study identifies areas that need improvement. The research findings emphasize the importance of teacher training, collaboration with related professionals, and increased community involvement to ensure the sustainability of inclusive education services.